Outcome-Based Curriculum: New approach for Higher Education Curriculum - Yanawongsa, Thitima; Intasingh, Somkiart; Nguenyuang, Sunee; Intanet, Nampueng (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2020)
Outcome-based education (OBE) is important and was used in the higher education curriculum development nowadays. Courses and teaching management which emphasize on student-learning outcomes was focused on. Curriculum development that emphasizes outcomes consists of two parts; outcomes and evaluation. Designing the learning outcomes begin with the vision and mission of the institution then specify course objectives, course outcomes and course level. Using learning outcomes to design courses, teaching plans, teaching methods and assessments at various levels with alignment to the course-level learning outcomes is not only an important idea to change the outcomes of education but also be able to development of advanced work force with specialized knowledge.